Day Old Vaccination Against Infectious Bursal Disease in Broiler Chickens - Hair-Bejo, M.; Ng, M.K.; Ng, H.Y. (International Journal of Poultry Science, 2004)
Infectious bursal disease (IBD) also known as Gumboro disease is an important viral disease in poultry industry due to significant economic losses resulting from high mortality and immunosuppression. The disease can only be controlled and prevented by proper vaccination and biosecurity. It was the objective of the study to determine the efficacy of an `intermediate` strain of live attenuated IBD vaccine in broiler chickens at day old vaccination. One hundred and fifty two day-old broiler chicks were reared and raised in slatted cage in experimental house. The chicks were divided into 3 groups namely the groups A, B and C. Both chicks in the group A (day old vaccination) and group B (day fourteen vaccination) were vaccinated with an `intermediate` strain of live attenuated IBD vaccine (104.5EID50/0.1ml) via intraocular route at day old and 14, respectively. The group C acted as the control. Eight chicks from each group A and group C were sacrificed at days 1, 7, 14, 21, 28, 35 and 42. The chicks in the group B were sacrificed at days 14, 21, 28, 35 and 42. The body weight of the sacrificed chicks was recorded and the blood samples were collected for IBD antibody titre using enzyme linked immunosorbent assays (ELISA). On necropsy, the gross pathological changes were recorded. The bursa of Fabricius was fixed in 10% buffered formalin for histological examination. The study showed that the body weight of chickens from all the three groups were not significant different (p>0.05) throughout the trial, except at day 14 and day 21 from group A was significantly lowered (p<0.05) than group C. The bursa weight and the ratio of bursa weight to body weight showed group B were significantly (p<0.05) lowered than group A and group C at days 28, 35 and 42. There were no bursa lesions in group A and group C throughout the experiment. However, moderate bursa lesions was observed in group B at days 21 and 28 of age and showed signs of recovery at days 35 and 42. Single dose of day old vaccination could not induce IBD antibody in the chickens. In contrast, vaccination at day 14 of age induced high and protective level of IBD antibody. The vaccine at both time of vaccination was able to neutralized high level of maternally derived antibody (MDA). It was concluded that single dose of day old vaccination in broiler chickens with high MDA (4821±509) was ineffective and could not induce IBD antibody.